Bahan Ajar Menulis Teks Fabel Bermuatan Nilai-Nilai Karakter Bagi Siswa Sekolah Menengah Pertama - Doni Wahyudin; Afnita Afnita (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2020)
This Research aims to produce a product that is fable text materials with character values to grade VII Junior high school students who are guided by the content, systematics, linguistic and certainly the design of the display. Data collection is carried out through a poll of the needs and test questionnaire of data analysis techniques consist of qualitative data analysis. Data analyzes qualitative verbal data obtained from interviews and written notes of suggestions and comments in the product feasibility test. The subject in this study is the development of character values for junior high school students, this research data source is a grade VII student and teacher in Development junior high school. It is deduced from the results of teacher and expert judgment and student responses. Once assessed the book is repaired according to the advice and input of students, teachers and experts so that the teaching materials are obtained according to the needs of students in the development of better life worth soul.